1999
DOI: 10.1046/j.1432-1327.1999.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents apoptosis in K562 cells by inhibiting lipoxygenase and cyclooxygenase activity

Abstract: The natural polyphenolic compound resveratrol (trans-3,4 H ,5-trihydroxystilbene) is shown to prevent apoptosis (programmed cell death) induced in human erythroleukemia K562 cells by hydrogen peroxide and other unrelated stimuli. Resveratrol reversed the elevation of leukotriene B 4 (from 6.40^0.65 to 2.92^0.30 pmol´mg protein 21 ) and prostaglandin E 2 (from 11.46^1.15 to 8.02^0.80 nmol´mg protein 21 ), induced by H 2 O 2 challenge in K562 cells. The reduction of leukotriene B 4 and prostaglandin E 2 correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 46 publications
4
105
1
2
Order By: Relevance
“…Preliminary observations from our group indicate that LTB 4 exerts catabolic activities on articular chondrocytes by decreasing matrix synthesis, which suggests that LTB 4 has a pathologic role in OA; however, relatively little is known about its effects on cartilage metabolism (35). Although the mechanism of resveratrolmediated inhibition of LTB 4 was not investigated in our study, it has been shown that resveratrol can also act as a potent inhibitor of the dioxygenase activity of LOX (36), the cell source of LTB 4 .…”
Section: Discussionmentioning
confidence: 90%
“…Preliminary observations from our group indicate that LTB 4 exerts catabolic activities on articular chondrocytes by decreasing matrix synthesis, which suggests that LTB 4 has a pathologic role in OA; however, relatively little is known about its effects on cartilage metabolism (35). Although the mechanism of resveratrolmediated inhibition of LTB 4 was not investigated in our study, it has been shown that resveratrol can also act as a potent inhibitor of the dioxygenase activity of LOX (36), the cell source of LTB 4 .…”
Section: Discussionmentioning
confidence: 90%
“…7 Resveratrol, an alleged natural cancer preventive agent present in red wine, 40 has been shown to inhibit PCD induced by unrelated stimuli in human erythroleukemia K562 cells, through competitive inhibition of 5-LOX and 15-LOX activity. 41 However, resveratrol is a general antioxidant which also inhibits nonenzymatic lipoperoxidation and cyclooxygenase activity 41 and acts as an agonist for the estrogen receptor. 42 Finally caffeic acid, which prevents apoptosis linked to 5-LOX activation, 15 is a LOX inhibitor with general antioxidant properties, 43 much like the 5-LOX inhibitor atocopherol.…”
Section: Lipoxygenase Involvement In Apoptotic Pathwaysmentioning
confidence: 99%
“…In rat liver microsomes, RS inhibited iron-induced as well as ultraviolet-irradiated lipid peroxidation and prevented LDL oxidation by copper (Fauconneau et al, 1997;Miura et al, 2000). RS could effectively prevent oxidative LDL modification by inhibiting lipoxygenase enzyme activity (Maccarrone et al, 1999;Kovanen and Pentikäinen, 2003). Polyphenols in red wine including RS have been reported to inhibit LDL oxidation; this effect was found to be stronger than the well-known anti-oxidant a-tocopherol .…”
Section: Inhibitory Effect Of Rs On Ros Production and Lipid Peroxidamentioning
confidence: 96%